PENDEKATAN ACCELERATED LEARNING DALAM PEMBELAJARAN QIRA’AH - Muhamad Fathoni (Jurnal Al-Manar, 2015)
Accelerated learning is a learning approach concerning with student psychology in their learning. It is a concept based on a finding of a Bulgarian psychiatrist, Dr. George Lozanov. Lozanov says that human brain, a main learning tool, can be effectively used only when it is "fun", not in pressure, free and comfortable. This learning approach has many elements which are called SAVI (Somatic, Auditory, Visual and Intellectual), learning which is involved whole brain to work. It is expected to actualize Qira'ah learning that is fun and motivates student to learn with no pressure.